The Effect of Project Based Learning Model assisted by Living Book Media on the Ability to Write Fable Story Texts for Students - Turnip, Berlian. R.; Marini, Netti; Untari, Ennis Noni; Siregar, Azrina Nabila; Mawarni, Mayasa Arditya (Program Pascasarjana UIN Sumatera Utara, 2025)
This study was motivated by the low ability of students in writing fable texts at Taman Asuhan Pematangsiantar Private Junior High School. The research aims to analyze the effect of the Project Based Learning model assisted by living book media on improving students' ability to write fable text. The method used is quantitative with a pseudo-experimental design. The research sample was 62 students who were divided into experimental and control groups. The main instruments were pre-test and post-test, with data analysis through t-test using SPSS. The results showed a significant increase in the experimental group compared to the control group. In conclusion, the Project Based Learning learning model assisted by living book is effective in improving the ability to write fable story text, as well as encouraging students' imagination, creativity, and active involvement in the learning process.